Sikap Rasul Paulus Terhadap Rintangan Pelayanan dalam Surat Filipi - Simanungkalit, Hulman (KERUGMA: Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
Abstract: Paul's opposition in the Epistle to Philippians is something interesting to study because this letter implies how to overcome the opposition that often arises in ministry. This letter is a letter written by the apostle Paul from prison, but this letter is a letter of joy that is able to encourage enthusiasm in the midst of the opposite situation. When the author conducted a study of this part of the book, there was a tremendous admiration for God and the determination and courage to keep preaching the Word according to God's will. The author is interested in highlighting this because it was inspired by the example of Paul who faced opposition in every ministry, especially in Philippi. The study of the selected text also considers that there are dynamics in the interpretation of the Philippians letter. Throughout history many theologians have undertaken this study, and continue to make their contribution. Likewise, the author feels the need to contribute as a form of active role in enriching the scientific treasures of theology students. Paul's opposition is explored through the steps of historical theological studies so that the meaning that is most appropriate to the depth of meaning intended by the author of the book is obtained.   Keywords: Gospel; envy; circumcision; enemy. Abstrak: Oposisi Paulus dalam Surat Filipi adalah sesuatu yang menarik yang dapat diteliti karena dalam surat ini tersirat cara mengatasi oposisi yang kerap timbul dalam pelayanan. Surat ini merupakan surat yang ditulis oleh rasul Paulus dari dalam penjara, namun surat ini merupakan surat sukacita yang mampu mendorong semangat ditengah-tengah situasi yang sebaliknya. Ketika penulis melakukan study atas bagian dari kitab ini, tumbuh kekaguman yang luar biasa akan Allah dan keteguhan hati serta keberanian untuk tetap memberitakan Firman sesuai dengan kehendak Tuhan. Penulis tertarik menyoroti hal ini dikarenakan terinspirasi terhadap teladan Paulus yang menghadapi para oposisi dalam setiap pelayanan khususnya di Filipi. Kajian atas teks yang dipilih juga mempertimbangkan bahwa terjadinya dinamika dalam penafsiran surat Filipi. Dalam sepanjang sejarah banyak teolog telah melakukan kajian ini, dan terus memberikan sumbangsih mereka. Demikian juga penulis merasa perlu memberikan kontribusi sebagai wujud peran aktif dalam memperkaya khazanah keilmuan mahasiswa teologi. Oposisi Paulus digali dengan langkah-langkah kajian historis teologis sehingga didapatkan makna yang paling sesuai dengan kedalaman arti yang dimaksud si penulis kitab.   Kata Kunci: Injil; dengki; sunat; seteru.